(untitled) (Global Journal of Medical Research, 2024)
Acute kidney injury AKI is one of the main secondary manifestations developed in patients with COVID-19 Based on this aspect the present study aimed to identify the main biomarkers used to predict acute kidney injury and prognosis in COVID-19 and gather information about the biomarkers studied Articles published in the Virtual Health Library between January 2020 and February 2022 in English Portuguese and Spanish were evaluated with the guiding question What is the scientific evidence on new biomarkers for diagnosis and determination of the prognosis of induced acute kidney injury in COVID-19 Initially more than 75 thousand articles were identified however with the attribution of inclusion and exclusion criteria 8 articles were selected and analyzed during the present study The findings of the present review emphasize that early diagnosis has a strong influence on the prognosis of AKI and that new biomarkers are useful for detecting and predicting the prognosis of the injury early The potential of these assays with new biomarkers proved to be significant and could allow their use in future research